A Comparison of Hydrogen Sintering and Phase Transformation (HSPT) Processing with Vacuum Sintering of CP‐Ti1. Issue 10 (20th June 2013) - Sun, Pei; Fang, Zhigang Zak; Koopman, Mark
<x xml:space="preserve">Abstract</x> The process of hydrogen sintering and phase transformation (HSPT) has previously been shown to produce Ti–6Al–4V with excellent mechanical properties. In the present work, titanium hydride powders are used to produce commercially pure Ti by both vacuum sintering and HSPT. Within the parameters of heat treatments applied, the HSPT samples exhibite finer microstructures, and show a 14% improvement in tensile strength and a 20% improvement in ductility compared to vacuum sintered samples. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>